'We are working in specialty units'-An exploratory qualitative study - Mphedziseni Esther Rangwaneni; Ndidzulafhi Selina Raliphaswa; Mary Maluleke; Vusiwana Patricia Letlalo; Thingahangwi Cecilia Masutha; Duppy Manyuma; Langanani Makhado; Tinyiko Nelly Rikhotso (Wiley, 2024)
Abstract Aim To explore related support needs of general nurses in specialty mental health units and provide references for formulating a model to support this population working in mental health care units. Design An exploratory qualitative design. Method In‐depth individual unstructured interviews were performed with 15 general nurses who worked in mental health care units and were selected through purposive sampling. Data were collected through in‐depth, individual, unstructured interviews. Data were analysed thematically using Tech's eight‐step analysis method. Results Two themes with their subthemes were extracted. The two themes included (a) Needs for professional growth and (b) the Need for emotional support. Conclusion Influenced by many factors, general nurses could not perform some nursing activities in mental health care units. Health managers should plan the training program to empower and provide emotional support to the general nurses in mental health care units. Further research is required to develop a model to facilitate the support of general nurses allocated to these units. Reporting Method This study follows the consolidated criteria for reporting qualitative research. Public Contribution A total of 15 general nurses participated in the study. We utilized their lunch time to conduct the interviews, significantly contributing to the article's content.